Blended scaffolding strategies through facebook for learning and improving the writing process and writing performance - Abdul Hameed Abdul Majid,; Siti Hamin Stapa,; Yuen, Chee Keong (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
The paper Learners today anticipate learning content to include some form of blended instruction that encourages either formal or informal collaboration in discovery oriented tasks. This study hinges on the sociocultural theory and the zone of proximal development (Vygotsky 1978) and Holton and Clarks (2006) scaffolding strategies. The study begins with a semi-structured interview given to 10 purposively selected participants from both experimental and control groups at the onset of the study to ascertain their perceptions about using blended scaffolding strategies through Facebook to aid learning and in improving the writing process and writing performance. The study continues for 14 weeks beginning with a pre-test for both groups. The experimental group i.e. the group using blended scaffolding strategies go through classroom teaching with the aid of computer technology and scaffolding using Facebook after school hours. The control group only goes through chalk and talk instruction. A post-test is administered at the end of 14 weeks to determine the effects of the treatment on the experimental group. Initial findings through the semi-structured interview regarding perceptions about using blended scaffolding strategies through Facebook to aid learning and in improving the writing process and writing performance favours the blended scaffolding strategies as a learning method compared to mere chalk and talk strategy.